2017
DOI: 10.18060/20856
|View full text |Cite
|
Sign up to set email alerts
|

Finding “Health” and “Meaning” in Texas-Sized Turnover: Application of Seminal Management Principles for Administration and Research in U.S. Public Child Welfare Agencies

Abstract: Keywords: Public child welfare; turnover; retentionTurnover has been identified as a major problem for public child welfare organizations (Weaver, Chang, Clark, & Rhee, 2007;Williams, Nichols, Kirk, & Wilson, 2011). Over the last 30 years, child welfare organizations have consistently struggled to develop new initiatives to improve workforce quality and stability (Ball & Dexheimer, 2015). In this paper we assert that it is time to examine the "problem" of turnover from a new perspective. By critically question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Family court is often perceived as a low-status setting in the legal system (Carnochan et al, 2007;Han et al, 2007). Lawyers and judges in family court cycle through the court quickly; this pattern is similar to the social work profession where there is also a high turnover rate, especially among child welfare workers (Carnochan et al, 2007;Han et al, 2007;Lizano & Mor Barak, 2015;Travis et al, 2016;Willis et al, 2016). An exploratory study found that the high turnover of legal professionals and social workers is a strong predictor of the effectiveness of inter-professional communication and collaboration (Han et al, 2007).…”
Section: Pay and Professional Statusmentioning
confidence: 99%
“…Family court is often perceived as a low-status setting in the legal system (Carnochan et al, 2007;Han et al, 2007). Lawyers and judges in family court cycle through the court quickly; this pattern is similar to the social work profession where there is also a high turnover rate, especially among child welfare workers (Carnochan et al, 2007;Han et al, 2007;Lizano & Mor Barak, 2015;Travis et al, 2016;Willis et al, 2016). An exploratory study found that the high turnover of legal professionals and social workers is a strong predictor of the effectiveness of inter-professional communication and collaboration (Han et al, 2007).…”
Section: Pay and Professional Statusmentioning
confidence: 99%
“…Through their research, Ellett, Ellis, Westbrook, and Dews (2007) have already established the structural persistence of such turnover. Willis, Chavkin, and Leung (2016) agree but go a step further to indicate that turnover is to be expected for a variety of reasons, some of which can be healthy for the agency. These authors describe means by which agencies work not to cut the rates of turnover but to reduce its impact on the agency.…”
mentioning
confidence: 93%
“…The field of child welfare is marked by longstanding workforce issues, including low case manager morale and high case manager turnover (Edwards & Wildeman, 2018;Strolin et al, 2006). In response to these challenges, researchers and policymakers have issued recommendations for reform (Briar-Lawson, 2014;Briar-Lawson & Zlotnick, 2003;Casey Family Programs, 2017;Pecora et al, 2018;Willis et al, 2016). Frequently absent from the process used to develop these recommendations is the perspective of case managers on what they need to effectively carry out their work tasks, what they need to be satisfied with their work, and what they need to remain on the job.…”
mentioning
confidence: 99%